Low Carbon Cities : Exploring New Crediting Approaches to Deliver Carbon and Climate Finance - World Bank Group (World Bank, Washington, DC, 2018)
By 2050, two-thirds of the planet’s population will live in urban centers, and nearly 90 percentof the 2.5 billion new urban dwellers will live in Africa and Asia. The world’s urban areas wereresponsible for around 70 percent of greenhouse gas (GHG) emissions in 2013, and that numbercould grow by 50 percent by 2050 if current trends continue. In 2015, world leaders committed to limiting the global temperature increase to well below 2 degrees Centigrade and to pursuing efforts to reach a 1.5 degrees Centigrade limit in the context of the Paris Agreement under the United Nations Framework Convention on Climate Change (UNFCCC). The Paris Agreement invitescities to scale up climate action, and over two-thirds of participating countries’ Nationally Determined Contributions (NDCs) mention urban action. More than 70 percent of the global low emissions and climate-resilient infrastructure will be built in urban areas, at an estimated cost of 4.5 to 5.4 trillion USD per year. As highlighted by the Cities Climate Finance Leadership Alliance (CCFLA), scarce climate finance resources must be used strategically to both increase the amount of funding available and as part of a process of enabling and levering existing and new financing to flow from a broad range of sources, most importantly from the private sector. It is essential for cities to diversify and blend their sources of finance and tap the full spectrum of resources available to raise funds for climate action. However, successful funding for climate action—notably in developing countries—needs to overcome barriers such as the lack of creditworthiness of subnational governments, insufficient access to capital markets and international mechanisms, and lack of financial and technical skills and human resources.